Studi Kelayakan Sumber Daya Air Baku Pulau Bintan – Tinjauan Aspek Kuantitas dan Kualitas - Dyah Marganingrum; Nyoman Sumawijaya; Arief Rachmat (Jurnal Wilayah dan Lingkungan, 2020)
The raw water feasibility is based on three aspects, such as quantity, quality, and continuity. This study aims to assess the feasibility of raw water on Bintan Island in quantity and quality terms The method used is a comprehensive analysis of hydrological and hydrogeological functions and water quality. The result of study shows that rainwater abundance in study location is not optimally stored as ground water due to limited catchment area and storage capacity of aquifer media which are dominated by rock units with low to moderate graduation rates (80%). The hydrogeology of study site is also dominated by local low productivity aquifer areas (70%) which are indicated by shallow aquifer layers. Therefore, the existence of reservoirs or storage is very important. The calculations results in 2017 show that raw water production of PDAM Tirta Kepri is 3,521,855 m3/year. While the community needs on Bintan Island in the same year amounted to 7,957,803 m3/year. Quality aspect analysis shows that the quality of well is lightly polluted (WQI = 0.59), while surface water is moderately polluted (WQI = 1.01). The parameter that gives the difference from two sources is iron content. Gibbs diagram analysis results show the weathering process by rainwater which erodes the land surface of bauxite mine and dissolves iron and flows along with runoff and into reservoirs. The potential for high iron pollution will increase often as Bintan Island is designated as a Special Economic Zone. Industrial and service activities will trigger acid rain which will cause a decrease in the value of rain pH and the process of dissolving iron on rocks and soil surfaces will increase.